The Relationship Between Unlimited Improvement and Business Performance: Educational Company - Elzawi̇, Hussin (Orhan KÜÇÜK, 2021)
This study was carried out with the aim to investigate the relationship between unlimited improvement and business performance in education /training businesses , Tech Global Company. After researching the review of literature in the area of business performance, the researcher became aware of the importance of such relationship between the two elements in the most of the sectors. A survey was conducted with managers and employees in the training business. This paper contains the following; firstly, it has been reviewed what was published about this subject. Secondly, the model of study was clarified and the data obtained from a total of 25 participants, which are the entire staff of the company, were analyzed. Thirdly, in the discussion and result sections the relationship between unlimited improvement and business performance was determined. And finally, according to this result, it is clear that there is a significant positive relationship between unlimited improvement and business performance.

Bu çalışma, Tech Global Company adlı eğitim/öğretim işletmelerinde sınırsız iyileştirme ile iş performansı arasındaki ilişkiyi araştırmak amacıyla yapılmıştır. Araştırmacı, iş performansı alanındaki literatür incelemesini araştırdıktan sonra, sektörlerin çoğunda iki unsur arasındaki bu tür bir ilişkinin öneminin farkına vardı. Eğitim işletmesinde yönetici ve çalışanlarla bir anket yapılmıştır. Bu kağıt şunları içerir; öncelikle bu konu ile ilgili yayınlanmış olanlar gözden geçirilmiştir. İkinci olarak, çalışmanın modeli netleştirilmiş ve şirketin tüm kadrosunu oluşturan toplam 25 katılımcıdan elde edilen veriler analiz edilmiştir. Üçüncü olarak, tartışma ve sonuç bölümlerinde sınırsız iyileştirme ile işletme performansı arasındaki ilişki belirlenmiştir. Ve son olarak, bu sonuca göre,.
Keywords: Unlimited Improvement; Business performance; Educational Company; İş Performansı; Eğitim Şirketi; Sınırsız iyileşme